Neck dissection in node negative oral malignancies: is it justified - Tote, Darshana S.; Jajoo, Suhas; A., Panchal; Tote, Sachin (International Journal of Advances in Medicine, 2017)
Background: Oral cancer is one of the ten most common cancers in world, prevalence being highest in India. The objective of the study was to decide whether it is justifiable to do neck dissection in every case of oral malignancy in true negative necks diagnosed by investigative modalities and to decide whether we can avoid unnecessary block dissection in patient of oral malignancy with negative necks diagnosed by investigation. Methods: It was proposed randomized controlled study conducted over period of 2 years including all patients diagnosed of having oral squamous cell carcinoma. Lymph nodes were assessed by clinical examination and ultrasonography (USG). FNAC was done with the help of USG guidance. After thorough evaluation, the patient was subjected for treatment either surgery or radiotherapy and sometimes chemotherapy. After neck dissection, whole block was sent for histopathological examination. Data collected was analysed on various statistical parameters. Results: For clinical examination consistency and fixity is having high reliability than size and shape. On USG central necrosis, ECS, shape and RI were having specificity and accuracy. Sensitivity, specificity and accuracy of USG FNAC is more. Conclusions: USG and USG FNAC are helpful methods in directing further work up in more efficient and cost-effective manner and these help in reaching diagnosis more accurately than the clinical examination alone and thus it is considered second step in evaluation of neck only after clinical examination.